Transverse prestressing and reinforced concrete as the key to restoration of masonry arch bridges. (15th October 2021) - Klusáček, Ladislav; Nečas, Radim; Požár, Michal; Pěkník, Robin; Svoboda, Adam
Abstract: There is still a large number of masonry arch bridges on the road and railway network. More than 80 % of arch bridges are over 100 years old so their service life has been exceeded significantly. The general focus of the paper is to show the method for strengthening and restoration of these bridges, especially if they have been damaged by longitudinal cracks. The restoration is performed using new spandrel walls from reinforced concrete stabilized by transverse prestressed cables. This paper illustrates the strengthening process with four examples of restored road or railway bridges. In addition, it includes examples of basic cable arrangements and a design of the new concrete walls, which are used as anchorage areas for transverse prestressing. The efficiency of this method will be determined using data measured during the prestressing and a load test. The measurements have shown an extremely favourable effect of the addition of horizontal prestressing within the new reinforced concrete walls. After an evaluation of the deformation of the top cross-section reduced up to 40 % of the values before strengthening. Highlights: Transverse prestressing of masonry structures. Restoration of old and historical masonry arch bridges. Unique system of stabilization and structural strengthening of arch masonry bridges damaged by longitudinal cracks. Field testing data verification using a newly invented mechanical amplifier designed for arch deformation measurement.